Magnetic and luminescent coordination networks based on imidazolium salts and lanthanides for sensitive ratiometric thermometry - Farger, Pierre; Leuvrey, Cédric; Gallart, Mathieu; Gilliot, Pierre; Rogez, Guillaume; Rocha, João; Ananias, Duarte; Rabu, Pierre; Delahaye, Emilie (Beilstein Journal of Nanotechnology, 2018)
The synthesis and characterization of six new lanthanide networks [Ln(L)(ox)(H2O)] with Ln = Eu3+, Gd3+, Tb3+, Dy3+, Ho3+ and Yb3+ is reported. They were synthesized by solvo-ionothermal reaction of lanthanide nitrate Ln(NO3)3·xH2O with the 1,3-bis(carboxymethyl)imidazolium [HL] ligand and oxalic acid (H2ox) in a water/ethanol solution. The crystal structure of these compounds has been solved on single crystals and the magnetic and luminescent properties have been investigated relying on intrinsic properties of the lanthanide ions. The synthetic strategy has been extended to mixed lanthanide networks leading to four isostructural networks of formula [Tb1−xEux(L)(ox)(H2O)] with x = 0.01, 0.03, 0.05 and 0.10. These materials were assessed as luminescent ratiometric thermometers based on the emission intensities of ligand, Tb3+ and Eu3+. The best sensitivities were obtained using the ratio between the emission intensities of Eu3+ (5D0→7F2 transition) and of the ligand as the thermometric parameter. [Tb0.97Eu0.03(L)(ox)(H2O)] was found to be one of the best thermometers among lanthanide-bearing coordination polymers and metal-organic frameworks, operative in the physiological range with a maximum sensitivity of 1.38%·K−1 at 340 K.
Keywords: coordination network; imidazolium salt; lanthanides; magnetism; thermometry

(untitled) - Moghadam, P. Z.; Li, A.; Wiggin, S. B.; Tao, A.; Maloney, A. G. P.; Wood, P. A.; Ward, S. C.; Fairen-Jimenez, D. (Chem. Mater., 2017)

(untitled) - Zhao, Y. (Chem. Mater., 2016)

(untitled) - Li, S.; Huo, F. (Nanoscale, 2015)

(untitled) - Pagis, C.; Ferbinteanu, M.; Rothenberg, G.; Tanase, S. (ACS Catal., 2016)

(untitled) - Yi, F.-Y.; Chen, D.; Wu, M.-K.; Han, L.; Jiang, H.-L. (ChemPlusChem, 2016)

(untitled) - Yao, Q.; Bermejo Gómez, A.; Su, J.; Pascanu, V.; Yun, Y.; Zheng, H.; Chen, H.; Liu, L.; Abdelhamid, H. N.; Martín-Matute, B.; Zou, X. (Chem. Mater., 2015)

(untitled) - Li, H.-Y.; Wei, Y.-L.; Dong, X.-Y.; Zang, S.-Q.; Mak, T. C. W. (Chem. Mater., 2015)

(untitled) - Li, B.; Wen, H.-M.; Cui, Y.; Qian, G.; Chen, B. (Prog. Polym. Sci., 2015)

(untitled) - Hu, Z.; Deibert, B. J.; Li, J. (Chem. Soc. Rev., 2014)

(untitled) - Cui, Y.; Chen, B.; Qian, G. (Coord. Chem. Rev., 2014)

(untitled) - Cui, Y.; Yue, Y.; Qian, G.; Chen, B. (Chem. Rev., 2012)

(untitled) - Rocha, J.; Carlos, L. D.; Paz, F. A. A.; Ananias, D. (Chem. Soc. Rev., 2011)

(untitled) - Heine, J.; Müller-Buschbaum, K. (Chem. Soc. Rev., 2013)

(untitled) - Allendorf, M. D.; Bauer, C. A.; Bhakta, R. K.; Houk, R. J. T. (Chem. Soc. Rev., 2009)

(untitled) - Amghouz, Z.; García-Granda, S.; García, J. R.; Ferreira, R. A. S.; Mafra, L.; Carlos, L. D.; Rocha, J. (Inorg. Chem., 2012)

Lanthanide Metal-Organic Frameworks - Fordham, S.; Wang, X.; Bosch, M.; Zhou, H.-C. (Lanthanide Metal-Organic Frameworks: Syntheses, Properties, and Potential Applications, 2014)

(untitled) - Rocha, J.; Brites, C. D. S.; Carlos, L. D. (Chem. – Eur. J., 2016)

(untitled) - Wang, Z.; Ananias, D.; Carné-Sánchez, A.; Brites, C. D. S.; Imaz, I.; Maspoch, D.; Rocha, J.; Carlos, L. D. (Adv. Funct. Mater., 2015)

(untitled) - García-García, A.; Oyarzabal, I.; Cepeda, J.; Seco, J. M.; García-Valdivia, A. A.; Gómez-Ruiz, S.; Salinas-Castillo, A.; Choquesillo-Lazarte, D.; Rodríguez-Diéguez, A. (New J. Chem., 2018)

(untitled) - Oyarzabal, I.; Fernández, B.; Cepeda, J.; Gómez-Ruiz, S.; Calahorro, A. J.; Seco, J. M.; Rodríguez-Diéguez, A. (CrystEngComm, 2016)

(untitled) - Seco, J. M.; Oyarzabal, I.; Pérez-Yáñez, S.; Cepeda, J.; Rodríguez-Diéguez, A. (Inorg. Chem., 2016)

(untitled) - Liu, K.; Li, H.; Zhang, X.; Shi, W.; Cheng, P. (Inorg. Chem., 2015)

(untitled) - Chen, M.; Sañudo, E. C.; Jiménez, E.; Fang, S.-M.; Liu, C.-S.; Du, M. (Inorg. Chem., 2014)

(untitled) - Decadt, R.; Van Hecke, K.; Depla, D.; Leus, K.; Weinberger, D.; Van Driessche, I.; Van Der Voort, P.; Van Deun, R. (Inorg. Chem., 2012)

(untitled) - Ma, R.; Chu, H.; Zhao, Y.; Wuren, Q.; Shan, M. (Spectrochim. Acta, Part A, 2010)

(untitled) - Wang, P.; Fan, R.-Q.; Liu, X.-R.; Wang, L.-Y.; Yang, Y.-L.; Cao, W.-W.; Yang, B.; Hasi, W.; Su, Q.; Mu, Y. (CrystEngComm, 2013)

(untitled) - Chai, X.-C.; Sun, Y.-Q.; Lei, R.; Chen, Y.-P.; Zhang, S.; Cao, Y.-N.; Zhang, H.-H. (Cryst. Growth Des., 2010)

(untitled) - Sequeira, G. M.; Tan, W. Y.; Moore, E. G. (Dalton Trans., 2015)

(untitled) - Abrahams, B. F.; Maynard-Casely, H. E.; Robson, R.; White, K. F. (CrystEngComm, 2013)

(untitled) - Han, L.; Zhang, S.; Wang, Y.; Yan, X.; Lu, X. (Inorg. Chem., 2009)

(untitled) - Farger, P.; Leuvrey, C.; Gallart, M.; Gilliot, P.; Rogez, G.; Rabu, P.; Delahaye, E. (Magnetochemistry, 2017)

Synthèse Ionothermale de Réseaux Hybrides Multiferroïques - Farger, P. (Université de Strasbourg, 2016)

(untitled) - Farger, P.; Guillot, R.; Leroux, F.; Parizel, N.; Gallart, M.; Gilliot, P.; Rogez, G.; Delahaye, E.; Rabu, P. (Eur. J. Inorg. Chem., 2015)

(untitled) - Martin, N. P.; Falaise, C.; Volkringer, C.; Henry, N.; Farger, P.; Falk, C.; Delahaye, E.; Rabu, P.; Loiseau, T. (Inorg. Chem., 2016)

(untitled) - Calderone, P. J.; Forster, P. M.; Borkowski, L. A.; Teat, S. J.; Feygenson, M.; Aronson, M. C.; Parise, J. B. (Inorg. Chem., 2011)

(untitled) - Ji, W.-J.; Zhai, Q.-G.; Li, S.-N.; Jiang, Y.-C.; Hu, M.-C. (Chem. Commun., 2011)

(untitled) - Morris, R. E. (Chem. Commun., 2009)

(untitled) - Xu, L.; Yan, S.; Choi, E.-Y.; Lee, J. Y.; Kwon, Y.-U. (Chem. Commun., 2009)

(untitled) - Zhang, J.; Chen, S.; Bu, X. (Angew. Chem., Int. Ed., 2008)

(untitled) - Xu, L.; Choi, E.-Y.; Kwon, Y.-U. (Inorg. Chem., 2007)

(untitled) - Fei, Z.; Zhao, D.; Geldbach, T. J.; Scopelliti, R.; Dyson, P. J. (Chem. – Eur. J., 2004)

(untitled) - Kühl, O.; Palm, G. (Tetrahedron: Asymmetry, 2010)

(untitled) - Deng, Z.-P.; Kang, W.; Huo, L.-H.; Zhao, H.; Gao, S. (Dalton Trans., 2010)

(untitled) - Wang, X.-J.; Cen, Z.-M.; Ni, Q.-L.; Jiang, X.-F.; Lian, H.-C.; Gui, L.-C.; Zuo, H.-H.; Wang, Z.-Y. (Cryst. Growth Des., 2010)

(untitled) - Zhao, X.-Q.; Liu, X.-H.; Li, J.-J.; Zhao, B. (CrystEngComm, 2013)

(untitled) - Dendrinou-Samara, C.; Tsotsou, G.; Ekateriniadou, L. V.; Kortsaris, A. H.; Raptopoulou, C. P.; Terzis, A.; Kyriakidis, D. A.; Kessissoglou, D. P. (J. Inorg. Biochem., 1998)

(untitled) - Deacon, G. B.; Phillips, R. J. (Coord. Chem. Rev., 1980)

Molecular Magnetism - Kahn, O. (Wiley-VCH, 1993)

(untitled) - Fisher, M. E. (Am. J. Phys., 1964)

(untitled) - Benelli, C.; Gatteschi, D. (Chem. Rev., 2002)

(untitled) - Cepeda, J.; Balda, R.; Beobide, G.; Castillo, O.; Fernández, J.; Luque, A.; Pérez-Yáñez, S.; Román, P. (Inorg. Chem., 2012)

(untitled) - Cañadillas-Delgado, L.; Pasán, J.; Fabelo, O.; Hernández-Molina, M.; Lloret, F.; Julve, M.; Ruiz-Pérez, C. (Inorg. Chem., 2006)

(untitled) - Han, Z.-B.; Zhang, G.-X.; Zeng, M.-H.; Ge, C.-H.; Zou, X.-H.; Han, G.-X. (CrystEngComm, 2009)

(untitled) - Lhoste, J.; Pérez-Campos, A.; Henry, N.; Loiseau, T.; Rabu, P.; Abraham, F. (Dalton Trans., 2011)

(untitled) - Andruh, M.; Bakalbassis, E.; Kahn, O.; Trombe, J. C.; Porcher, P. (Inorg. Chem., 1993)

Theoretical Foundations of Molecular Magnetism - Boča, R. (Elsevier, 1999)

(untitled) - Amar, N. B.; Hassairi, M. A.; Dammak, M. (J. Lumin., 2016)

(untitled) - Liu, G. K.; Carnall, W. T.; Jones, R. P.; Cone, R. L.; Huang, J. (J. Alloys Compd., 1994)

(untitled) - Bernini, M. C.; Brusau, E. V.; Narda, G. E.; Echeverria, G. E.; Pozzi, C. G.; Punte, G.; Lehmann, C. W. (Eur. J. Inorg. Chem., 2007)

(untitled) - Ananias, D.; Kostova, M.; Almeida Paz, F. A.; Ferreira, A.; Carlos, L. D.; Klinowski, J.; Rocha, J. (J. Am. Chem. Soc., 2004)

Lanthanide Probes in Life, Chemical and Earth Sciences - Bünzli, J.-C. G.; Choppin, G. R. (Elsevier, 1989)

(untitled) - Cui, Y.; Xu, H.; Yue, Y.; Guo, Z.; Yu, J.; Chen, Z.; Gao, J.; Yang, Y.; Qian, G.; Chen, B. (J. Am. Chem. Soc., 2012)

(untitled) - Brites, C. D. S.; Lima, P. P.; Silva, N. J. O.; Millán, A.; Amaral, V. S.; Palacio, F.; Carlos, L. D. (Nanoscale, 2012)

(untitled) - Cadiau, A.; Brites, C. D. S.; Costa, P. M. F. J.; Ferreira, R. A. S.; Rocha, J.; Carlos, L. D. (ACS Nano, 2013)

(untitled) - Zhou, Y.; Yan, B.; Lei, F. (Chem. Commun., 2014)

(untitled) - Cui, Y.; Song, R.; Yu, J.; Liu, M.; Wang, Z.; Wu, C.; Yang, Y.; Wang, Z.; Chen, B.; Qian, G. (Adv. Mater., 2015)

(untitled) - Zhou, Y.; Yan, B. (J. Mater. Chem. C, 2015)

(untitled) - Zhao, D.; Rao, X.; Yu, J.; Cui, Y.; Yang, Y.; Qian, G. (Inorg. Chem., 2015)

(untitled) - Li, L.; Zhu, Y.; Zhou, X.; Brites, C. D. S.; Ananias, D.; Lin, Z.; Paz, F. A. A.; Rocha, J.; Huang, W.; Carlos, L. D. (Adv. Funct. Mater., 2016)

(untitled) - Yang, Y.; Chen, L.; Jiang, F.; Yu, M.; Wan, X.; Zhang, B.; Hong, M. (J. Mater. Chem. C, 2017)

(untitled) - Chuasaard, T.; Ngamjarurojana, A.; Surinwong, S.; Konno, T.; Bureekaew, S.; Rujiwatra, A. (Inorg. Chem., 2018)

(untitled) - Yang, Z.; Cao, J.; He, Y.; Yang, J. H.; Kim, T.; Peng, X.; Kim, J. S. (Chem. Soc. Rev., 2014)

(untitled) - Altomare, A.; Cascarano, G.; Giacovazzo, C.; Guagliardi, A.; Burla, M. C.; Polidori, G.; Camalli, M. (J. Appl. Crystallogr., 1994)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A: Found. Crystallogr., 2008)

SHELXS-97, Program for Crystal Structure Solution (University of Göttingen, 1997)

(untitled) - Farrugia, L. J. (J. Appl. Crystallogr., 1999)

(untitled) - Macrae, C. F.; Edgington, P. R.; McCabe, P.; Pidcock, E.; Shields, G. P.; Taylor, R.; Towler, M.; van de Streek, J. (J. Appl. Crystallogr., 2006)

DIAMOND (Crystal Impact GbR, 1999)